Perfomance analysis of libraries for testing web applications on the ASP.NET Core platform - Karol Niedziela; Jakub Nieradko (Journal of Computer Sciences Institute)
This paper conducts a performance analysis of three libraries: XUnit, NUnit, MSTest, aiming to compare the time performance. The performance was checked using load test, synchronous and asynchronous tests. The synchronous and asynchronous tests were divided into groups of 10, 25, 50 and 100 test cases. The tests were carried out using an inhouse project written on the ASP.NET Core platform.